A New Genus and Species of Nematode (Oxyurida, Thelastomatoidea) from the Chinese Medicinal Cockroach, Eupolyphaga sinensis (Walker, 1868) - Qingren Zeng; Hao Yuan; Xueying Liu; Fanming Meng (Zoonoses, 2024)
A new nematode was found during a survey of the microbiota and parasites of the Chinese medicinal cockroach, Eupolyphaga sinensis (Walker, 1868) in China. The nematodes were sampled from E. sinensis , which were collected in a rural area of Hunan province. Adult nematodes of both sexes were observed in detail using light and scanning electron microscopy. Phylogenetic analysis was performed based on 28S and 18S gene sequences of this species and all the available species sequences (> 500 bp) from the Thelastomatoidea superfamily to generate a more robust topologic structure of phylogenetic evolutionary reconstruction. This nematode is markedly distinguished from all reported members of the Thelastomatidae by several morphological characters. A combination of morphological and molecular studies indicates that this new nematode formed an independent branch parallel to the group of Thelastoma under Thelastomatidae. The nematode presented herein is identified as a new species namely Corydiinema hunanensis sp. nov. and belongs to a new genus, Corydiinema gen. nov. within Thelastomatidae.